Preference and willingness to pay of female college students for human papillomavirus vaccination in Zhejiang Province, China: A discrete choice experiment - Ying Wang; Yu Hu; Yaping Chen; Hui Liang (Taylor & Francis Group, 2021)
The study aimed to quantify the preferences of female college students for human papillomavirus (HPV) vaccination in Zhejiang Province, China, using a discrete choice experiment (DCE). One medical college and one nonmedical college were selected using convenience sampling, and the respondents were identified using stratified cluster sampling. A DCE focused on vaccine-related and service-related attributes was conducted in 2019. Latent class analysis was used to estimate the vaccine-related attributes, and conditional logistic regression was used to construct the choice model for the service-related attributes. In total, 850 female college students finished the study. Two latent classes were identified. Those who had more knowledge of HPV and felt more pressure about the related infection and diseases had a significantly higher chance of belonging to class 1 and were more likely to choose vaccination (percentages of respondents choosing no vaccination was 1.1% in class 1 versus 84.7% in class 2, χ2 = 641.1, P < .01). There were 742 respondents who chose vaccination in vaccine-related scenes, and 98.8% of them still chose to receive the vaccine in service-related scenes. Ways of making an appointment, number of weeks waiting for vaccination, service time for vaccination, time to the nearest vaccination site, and added cost all impacted the probability of choosing HPV vaccination services. It is concluded that higher levels of HPV knowledge and sociopsychological pressure led to a higher probability of HPV vaccination uptake in China. It is necessary to disseminate proper knowledge of HPV to improve the coverage and equality of HPV vaccination.